Tufts baseball team on steps of Barnum hall - Unknown (Tufts Archival Research Center, 2008)
8x10. Players identified by last name only. Back row: Harris (Mgr.), Proctor, Atwater (Asst. Mgr.); middle row: Angell, Adams, Bennett, Ruthford, Coach Laurie; front row: Jameson, Marzynski, Hooper (Capt.), Quatlers, Lee.